Association of perceived interest major fit and objective interest major fit with academic achievement - Vahidi, Naghmeh; Roslan, Samsilah; Abdullah, Maria Chong; Omar, Zoharah (Australian International Academic Centre, 2016)
Recently, despite the high budget allocating for education in Malaysia, the educational performance among students is low (Blueprint, 2013). Pascarella and Terenzini (2005; 1991) have identified four theories and models that affect students’ learning: (a) psychosocial, (b) cognitive-structural, (c) typological, and (d) person-environment interaction. This study focuses on person-environment interaction. The interactionist approach emphasizes that neither personal characteristics nor situational factors alone are unable to identify the attitudes or responses of people, but the interaction of them can be highly influential (Schneider, 1982; Terborg, 1981). Person-environment fit arguments were raised by interactionists who discussed that particulars attitudes, behaviours and cognitions are the results of the interaction between situational factors and individuals (Chatman, 1989; Muchinsky & Monahan, 1987; Ostroff & Schulte, 2007). The present study used academic achievement that is one of the outcomes of person–environment (P–E) fit. This research employed different types of P-E fit such as objective and perceived interest major fit. The main aim of the present study is to examine the relationship between the P-E fit and academic achievement. The present study is carried out in The Universiti Putra Malaysia (UPM). The participants of the study were 2503 undergraduate students of 12 faculties at UPM. Findings of the relationship between the P-E fit and academic achievement have shown a highly positive relationship between the perceived interest major fit and the academic achievement, but there is no significant relationship between the objective interest major fit and the academic achievement.